Using the swarm intelligence algorithms in solution of the two-dimensional inverse Stefan problem. (February 2015) - Hetmaniok, Edyta; Słota, Damian; Zielonka, Adam
Abstract In the paper a procedure for solving the two-dimensional inverse Stefan problem is presented. In considered problem the heat transfer coefficient is identified with the aid of known measurements of temperature in selected points of the region as the additional information. Direct Stefan problem is solved by using the alternating phase truncation method. Goal of the paper is to compare two swarm intelligence algorithms–the Ant Colony Optimization algorithm and the Artificial Bee Colony algorithm–applied for minimizing a functional expressing the error of approximate solution.